2009
DOI: 10.1021/ja902552m
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reactivity of Ru-Based Metathesis Catalysts with a π-Acid Ligand Trans to the Ru−Ylidene Bond

Abstract: In this work we explore the reactivity induced by coordination of a CO molecule trans to the Ru-ylidene bond of a prototype Ru-olefin metathesis catalyst bearing the N-heterocyclic carbene (NHC) ligand SIMes. Static DFT calculations indicate that CO binding to the Ru center promotes a cascade of reactions with very low energy barriers that lead to the final crystallographically characterized product, in which the original methylidene group has attacked the proximal aromatic ring of the SIMes ligand leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 87 publications
0
42
0
Order By: Relevance
“…Cavallo et al illuminated the key role of the π−acid CO ligand for promoting the reactivity of the Ru−olefin metathesis catalyst. 84 We also investigated the changes in the spin state and electronic structure of the PAH-supported Pt atom and dimer due to adsorption of the CO molecule. As shown in Figure 4, the spin ground state of the CO−Pt 2 /PAH complex is the singlet state, and the triplet state is higher in energy for all configurations.…”
Section: Co Adsorption On Carbon-supported Pt Atom and Dimermentioning
confidence: 99%
“…Cavallo et al illuminated the key role of the π−acid CO ligand for promoting the reactivity of the Ru−olefin metathesis catalyst. 84 We also investigated the changes in the spin state and electronic structure of the PAH-supported Pt atom and dimer due to adsorption of the CO molecule. As shown in Figure 4, the spin ground state of the CO−Pt 2 /PAH complex is the singlet state, and the triplet state is higher in energy for all configurations.…”
Section: Co Adsorption On Carbon-supported Pt Atom and Dimermentioning
confidence: 99%
“…In this respect, it is worth noting that the position trans to the Ru-ylidene bond has been scarcely considered during the years [24,25,[32][33][34]. For example, Grubbs and coworkers have suggested that one of the ortho-F atoms of the NHC A shown in Scheme 2 could be engaged in an interaction with the Ru center that results in increased metathesis activity [35].…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, the deactivation reaction of Scheme 1 illustrates that the coordination position trans to the Ru-ylidene bond is not ''innocent'' and can trigger interesting reactivity. For this reason, we investigated the mechanism of deactivation shown in Scheme 1 in case of the Ru-methyidene bond [32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations